Industrial progress and economic growth - Nawal Kishore Singh (New Delhi, 1982)
The present study aims at analysing the trends of industrialization and economic growth in Bihar during the plan period, with a view to ascertaining whether, in the matter of all round progress, this State has kept pace with other States or has lagged behind. It examines the developmental programmes undertaken by the Government and private individuals as also the incentives provided by the Government to the private entrepreneurs by way of subsidies, provision of infrastructural facilities and other fiscal and monetary disciplines.
Keywords: Economic growth